2019
DOI: 10.3389/fgene.2019.01001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sperm Methylation at LINE-1, Four Candidate Genes, and Nicotine/Alcohol Exposure With the Risk of Infertility

Abstract: In this study, we examined whether smoking and drinking affect sperm quality and the DNA methylation of the repetitive element LINE-1, MEST, P16, H19, and GNAS in sperm. Semen samples were obtained from 143 male residents in a minority-inhabited district of Guizhou province in southwest China. Quantitative DNA methylation analysis of the samples was performed using MassARRAY EpiTYPER assays. Sperm motility was significantly lower in both the nicotine-exposed (P = 0.0064) and the nicotine- and alcohol-exposed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The field of human reproduction is no exception in following this trend, as studying epigenetic changes in gametes is even more interesting considering that gametes are responsible for transferring genetic material to the next generation 11 . Lately, a number of studies exploring sperm DNA methylation from different angles have been published, 12‐18 but there is a lack of studies on how different sperm preparation methods could possibly influence the sperm DNA methylation profile. To our knowledge, only one study has explored the DNA methylation profile of spermatozoa after DGC sperm preparation, 22 which is one of the most often used sperm preparation method in assisted reproduction 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of human reproduction is no exception in following this trend, as studying epigenetic changes in gametes is even more interesting considering that gametes are responsible for transferring genetic material to the next generation 11 . Lately, a number of studies exploring sperm DNA methylation from different angles have been published, 12‐18 but there is a lack of studies on how different sperm preparation methods could possibly influence the sperm DNA methylation profile. To our knowledge, only one study has explored the DNA methylation profile of spermatozoa after DGC sperm preparation, 22 which is one of the most often used sperm preparation method in assisted reproduction 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this can affect the outcome of in vitro fertilization (IVF) procedures in terms of abnormal embryogenesis and pregnancy rates 13,14 . In studies on sperm DNA methylation, whole‐genome methylation analysis can be performed 13‐15 but often, only particular regions or genes are examined exclusively, for instance, regions and genes that are known to have specific paternal or maternal imprinting 16‐18 . Thus, these genes or regions are expressed only from one parental allele and around 100 such imprints have been found in mammalian genomes 19 …”
Section: Introductionmentioning
confidence: 99%
“…It is unclear in what way the sperm epigenome is sensitive to potential mutagens and how these factors impact fertility parameters. Recent investigations have confirmed a link between potentially damaging agents and disruption to epigenetic processes [ 92 , 93 ], however, several studies have reported controversial results [ 94 ].…”
Section: Reasons and Consequences Of Genome Instabilitymentioning
confidence: 99%
“…The DMRs are established during gametogenesis at imprinted and non-imprinted loci and are susceptible to environmental factors [65,66]. LINE-1 methylation in sperm could be a risk marker of infertility in man at nicotine/alcohol exposure [67]. It is also possible to alter DNA methylation levels and patterns within intact mammalian cells by treatment with various chemical inhibitors, DNA-demethylating drugs, which have recently been introduced as potential therapeutic agents for the treatment of human diseases, particularly myelodysplastic syndromes [68].…”
Section: Dna Methylation During Gametogenesis and Embryogenesismentioning
confidence: 99%
“…The dynamic reprogramming and other epigenetic patterns which could affect normal patterns of gene expression/genome stability during development could lead to an increased risk of CAs or complex diseases later in life [65][66][67].…”
Section: Dna Methylation During Gametogenesis and Embryogenesismentioning
confidence: 99%